The significance of product design in the circular economy: A sustainable approach to the design of data centre equipment as demonstrated via the CEDaCI design case study. (2022) - Kerwin, Kristina; Andrews, Deborah; Whitehead, Beth; Adibi, Naeem; Lavandeira, Silvio
Abstract: Society depends on fast, uninterrupted 24/7 data transfer in almost every aspect of our lives. Data centres (DC) across the globe process billions of gigabytes of data every day. There are currently about 7 million data centres globally and the sector is expected to grow fivefold by 2030, inevitably increasing already high demand for millions of tonnes of resources, including critical raw materials (CRM). The infrastructure for recycling sectoral waste is lacking, wasting millions of tonnes of materials. Many virgin materials are located in conflict zones, which jeopardises the supply chain that the sector heavily relies on, consequently posing a danger of severe material shortages in the future. Present design thinking does not balance optimisation of the performance and operational energy requirements and designing for circularity. To date, server design has mainly been focused on energy efficiency. However, a Circular Economy (CE) entails consideration of a complete life cycle of the product, including embodied impacts. Because sectoral data processing and energy requirements continue to grow, sustainable design and innovation in line with the 2020 EU Circular Economy Action Plan are crucial in promoting best practices and managing the sector's energy demand in the future. This paper describes a proposed sustainable server design developed as part of the CEDaCI (a Circular Economy for the Data Centre Industry) project and based on the design requirements outlined by the EU Circular Economy Action Plan 2020 together with other directives. It presents recommendations for good practice methods, futureproofing data centre equipment design for a Circular Economy and building a critical foundation for sustainable hardware design that can be developed in the future.